PENERAPAN PENDEKATAN RESTORATIVE JUSTICE PADA KASUS KEKERASAN TERHADAP ANAK (ANALISIS KASUS : PENGANIAYAAN ANAK USIA 12 TAHUN OLEH AYAH KANDUNG DI KEC. MEDAN AMPLAS) - Firnanda, Wahyuni; Nasution , Abdul Halim; Anastasya, Windy; Daulay, M. Nasir; Hidayat, Syarif; Putra, Ramadhana; Saddad, Muhammad Suharqyman; Abdinata, Abdinata (Gapenas Publisher, 2025)
The restorative justice approach is an alternative to case resolution that emphasizes the restoration of relationships between victims, perpetrators, and the community, as well as providing opportunities for perpetrators to take responsibility and correct the mistakes that have been made. In this case, the research explores the process and mechanism of implementing restorative justice, starting from the identification of problems, the involvement of related parties (victims, perpetrators, families, communities, and related institutions), to the remedial steps taken. This study aims to analyze legal protection for children victims of violence and the application of the restorative justice approach in resolving cases of violence against children, especially in the case of abuse of a 12-year-old child by a biological father in Medan Amplas District. The results of the study show that children as victims of violence have certainly been given legal protection by the government which is manifested in the form of legal provisions and the application of the law that. Meanwhile, the restorative justice approach as a form of dispute resolution process can be a constructive solution in reducing the long-term impact on children victims of violence and providing opportunities for perpetrators to make changes. Overall, the application of restorative justice in cases of violence against children can be an important step in creating more sustainable justice and rebuilding relationships within affected families.